2015
DOI: 10.5897/ajbm2013.7299
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between some demographic variables and leadership effectiveness among local government managers in South Africa

Abstract: Scholars have argued that demographic variables are critical factors that could also be used together with other factors to explain the variances in the behaviour of effective leaders. They are very significant to virtually all kinds of modern organizations. The current workforce is increasingly getting younger and highly educated. And an increasing proportion of female managers are also found in today's organizations. The present study therefore, explored the relationship between some demographic variables an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Research by [34] conducted in Singapore found that outcomes from leadership behaviors such as productivity and satisfaction are higher for those who are older and have been working for their organizations for a longer time. [35] argued that age is related to the effectiveness of leadership, suggesting that managements and leaders should consider age diversity while practicing leadership. On the other hand, the present study's finding is contradicted with [36]'s research.…”
Section: Discussionmentioning
confidence: 99%
“…Research by [34] conducted in Singapore found that outcomes from leadership behaviors such as productivity and satisfaction are higher for those who are older and have been working for their organizations for a longer time. [35] argued that age is related to the effectiveness of leadership, suggesting that managements and leaders should consider age diversity while practicing leadership. On the other hand, the present study's finding is contradicted with [36]'s research.…”
Section: Discussionmentioning
confidence: 99%
“…In supporting this view, some scholars highlighted that it is difficult to attach student satisfaction with educational outcome since satisfaction is a reflection of the students' perception on their educational experiences, further fuelled by feelings, emotions and subjective attitudes (Summers, Waigandt, & Whittaker, 2005;Baron & Corbin, 2012). Bell et al (2015) argued that due to the emergence of a younger and highly educated workforce, a leader who can deeply connect with them is a necessity. Three demographic profile variables were proposed: gender, age and education.…”
Section: Leadershipmentioning
confidence: 99%
“…Needless to say, these decisions are vital to the universities' success. Of course, sound decisions are mostly based on logic, experience and information, but what many people do not know is that these decisions are also inherently motivated by the individual's characteristics (Jones & Bekhet, 2015;Bell, Rvanniekerk, & Nel, 2015).…”
Section: Introductionmentioning
confidence: 99%